Evaluasi Program Pendidikan Karakter Di MI Arohmah Keraksaan-Probolinggo - Muhammad Rafli Salim; Mutiara Saridewi (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
Character education at MI Arohmah is an effort that is systematically designed and implemented to help students understand the values of human behavior related to God, self, fellow human beings, the environment, and nationality which are manifested in thoughts, attitudes, feelings, words, and actions based on religious norms, laws, manners, culture, and customs. The purpose of this study was to describe and evaluate the implementation or achievement of the Character Education Program at Mi Arohmah. This type of research uses the CIPP model, namely context, input, process, and product as an evaluation tool evaluated through qualitative research methods with a case study type approach. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis in the research was carried out through the stages of analyzing data collection, data compaction, data presentation, data verification. Checking the validity of the data in the research is the expansion of involvement, persistence of observation, and triangulation. The results showed that the character education project was in the good category. Then in the character education program evaluation value based on the four stages of the CIPP model, it gets a good category in the context stage, a good category in the input stage, a very good category in the process stage, and a good category in the product stage.